A new model that using transfer stations for straw collection and transportation in the rural areas of China: A case of Jinghai, Tianjin. (December 2016) - Cao, Jie; Pang, Bin; Mo, Xiaoping; Xu, Fangyan
Abstract: Obtaining sufficient raw material and controlling straw transportation costs are two critical factors in planning new straw utilization factories. So we develop a straw collection and transportation model using transfer stations and propose a method to calculate the corresponding transportation costs based on China's specific agricultural and rural transportation conditions in this paper. We also present a case study showing how to build a straw collection and transportation system for a planned straw-coal power plant. In this model, villages are the smallest collection units. Therefore, we consider both the uneven distribution of straw and the fact that, in China, straw is gathered within each village. The straw collection area is divided into a grid, in which each grid cell may be selected to build a transfer station within it. Building the appropriate number of transfer stations and optimizing their locations will help to reduce transportation costs. The difference between utilizing highways and rural roads for transportation is also considered. Transportation cost calculations and location optimization for each transfer station are carried out in ArcMap. This model can be used to help any facility requiring straw to obtain it steadily at a low transportation cost. This study also has important relevance to the location distribution of straw consumption factories. Highlights: A village – transfer station – factory straw collection and transportation model is developed, and the locations of the transfer stations are optimized to reduce the transportation cost. The problem of uneven distribution of straw resources is addressed by taking villages as the smallest collection units. The difference between highway transportation and rural roads is considered when calculating the transportation cost.